Transcriptional Control of Hypoxic Hyphal Growth in the Fungal Pathogen Candida albicans - Henry, Manon; Burgain, Anaïs; Tebbji, Faiza; Sellam, Adnane (Frontiers in Cellular and Infection Microbiology, 2022)
The ability of Candida albicans, an important human fungal pathogen, to develop filamentous forms is a crucial determinant for host invasion and virulence. While hypoxia is one of the predominant host cues that promote C. albicans filamentous growth, the regulatory circuits that link oxygen availability to filamentation remain poorly uncharacterized. We have undertaken a genetic screen and identified the two transcription factors Ahr1 and Tye7 as central regulators of the hypoxic filamentation. Both ahr1 and tye7 mutants exhibited a hyperfilamentous phenotype specifically under an oxygen-depleted environment suggesting that these transcription factors act as negative regulators of hypoxic filamentation. By combining microarray and ChIP-chip analyses, we have characterized the set of genes that are directly modulated by Ahr1 and Tye7. We found that both Ahr1 and Tye7 modulate a distinct set of genes and biological processes. Our genetic epistasis analysis supports our genomic finding and suggests that Ahr1 and Tye7 act independently to modulate hyphal growth in response to hypoxia. Furthermore, our genetic interaction experiments uncovered that Ahr1 and Tye7 repress the hypoxic filamentation via the Efg1 and Ras1/Cyr1 pathways, respectively. This study yielded a new and an unprecedented insight into the oxygen-sensitive regulatory circuit that control morphogenesis in a fungal pathogen.